The effects of oil and gold prices on oil-exporting countries - Bildirici, Melike E.; Sonustun, Fulya Ozaksoy (ELSEVIER SCIENCE BV, 2018)
Gold and oil prices have wide impacts on the determinants of financial, commodity, labor markets and industrial production of countries because of high liquidity and tradability. Gold and oil price volatility implications are crucial for the economic growth of both emerging and developed countries across the world. By this motivation, in this paper, firstly, it is aimed to determine the asymmetric relationship between gold and oil prices which is strongly related with macroeconomic dynamics and business cycle structure of the countries. And secondly, their effects on the economic growth of the selected oil exporter countries (Canada, China, Kuwait, Mexico, Saudi Arabia, United Arab Emirates, United Kingdom, the United States of America) were examined by using MS-(V)AR methods. These methods are employed to test the impact of gold and oil price prices' volatilities on each other, to identify the business cycle structures and make the effective economic policy inferences for each of the selected countries. Transition probabilities of the regimes emphasized the asymmetric behavior of business cycles. More critically, the findings revealed the importance of gold and oil prices volatilities on economic growth and oil prices have effective role on determining business cycle of the countries.
Keywords: Volatility of oil and gold prices; MS-AR(X) analysis; MS-VARX analysis; CRUDE-OIL; ECONOMIC-ACTIVITIES; SAFE HAVEN; MACROECONOMY; ENERGY; DEMAND; SHOCKS; HEDGE; INCREASES; INFLATION; Energy & Fuels